J. G. Kohl papers - Kohl, J. G. (Johann Georg), 1808-1878.
Holograph manuscripts by Kohl entitled "History of the Discovery and Exploration of the Gulf of Mexico," "A Catalogue of Books Relating to the History of the East Coast of the United States from the Year 1519-1855," and "An Historical List of the Names of the Counties, Oceanic Sections, Bays, Inlets, Harbours, Ports, Cities, Rivermouths, Islands, Capes, Banks, etc. etc. on the Atlantic or East Coast of the United States."
Microfilm edition available
Microfilm produced from originals in the Manuscript Division.
Author and geographer.
Collection material in English.
Keywords: Bibliography; Atlantic Coast (U.S.) -- Geography; Mexico, Gulf of -- Discovery and exploration; Authors; Geographers